The Role of the Police in Mitigation and Prevention Efforts to Reduce Crime Rates in Sorong City - Laode Muhammad Arief; Hadi Tuasikal; Marlino Novlyson Luhukay (Faculty of Law, Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the role of the Sorong City Police in combating and preventing criminal acts to reduce crime rates in Sorong City, as well as to identify the obstacles encountered in its implementation. The method used is an empirical legal study, employing a field-based approach through in-depth interviews with the Criminal Investigation Unit (Satreskrim) of the Sorong City Police and analysis of crime data from 2021 to 2024. The novelty of this study lies in its comprehensive analysis of post-pandemic fluctuations in crime rates in the specific region of Sorong City, as well as its evaluation of the effectiveness of an integrated strategy combining conventional repressive measures with a Restorative Justice approach at the city police department level. The results of the study indicate that the Sorong City Police have implemented preemptive, preventive, and repressive strategies in an integrated manner, as evidenced by a stable crime clearance rate above 80% despite significant fluctuations in the number of reported cases. The conclusion of this study is that although police efforts have been optimal in law enforcement, the overall effectiveness of crime prevention is still hampered by limitations in human resources, infrastructure, and the economic conditions of the community that fuel crime. More intensive collaboration between the police, local government, and community leaders is needed to strengthen the communaity safety system.